The Impact of Environmental Externalities on Commodity Price Stability: GARCH (Generalized Autoregressive Conditional Heteroskedasticity) Volatility Analysis - Eki Dudi Darmawan (PT. Anagata Sembagi Education, 2025)
Crude oil is a highly strategic global commodity whose price is extremely sensitive to external dynamics and economic shocks. This study aims to analyze the effect of environmental externalities on crude oil price volatility by applying the Generalized Autoregressive Conditional Heteroskedasticity (GARCH) model. Secondary data consisting of daily West Texas Intermediate (WTI) crude oil prices from January 2015 to December 2024 were examined using the ADF test, ARCH–LM test, model selection based on AIC and BIC, and parameter estimation of GARCH(1,1). The results indicate that environmental externalities have a positive and significant effect on crude oil price volatility, as evidenced by the γ coefficient of 0.227 and the α + β value of 0.905, demonstrating long-term volatility persistence. These findings show that crude oil price stability is determined not only by traditional supply and demand factors but also by global environmental regulations, emission policies, and energy transition dynamics. This study provides empirical contributions to energy economics research and practical insights for policymakers in developing energy security strategies that are adaptive to the sensitivity of global commodity prices.